2010
DOI: 10.1016/j.jvs.2009.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Functional adaptation of venous smooth muscle response to vasoconstriction in proximal, distal, and varix segments of varicose veins

Abstract: Background Varicose Veins (VarV) is a common disorder of venous dilation and turtuosity with unclear mechanism. Although venous smooth muscle constitutes a significant component of the vein wall, the functional integrity and the ability of various regions of the VarV to constrict is unclear. The objective of this study was to test the hypothesis that the different degrees of venodilation in different regions of VarV reflect segmental differences in the responsiveness to receptor-dependent vasoconstrictive stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The control group included great saphenous vein samples from patients undergoing lower limb bypass operations or amputations in addition to vein samples from other anatomical locations such as the neck and lower abdomen, which are subject to different biomechanical stresses than the GSV. While statins and most other cardiovascular medications have a short half-life (less than 24 hours) 24 and neither parent drugs nor their metabolites were detected in our NMR or LCMS based profiling, it is possible that the above factors confounded the presented results by pharmacological effect. It is, nonetheless, important to stress that despite these issues the varicose vein samples were consistently different from the control groups in the statistical modelling, suggesting that any variability within the non-varicose veins groups was far outweighed by the differences between the two groups.…”
Section: Discussionmentioning
confidence: 89%
“…The control group included great saphenous vein samples from patients undergoing lower limb bypass operations or amputations in addition to vein samples from other anatomical locations such as the neck and lower abdomen, which are subject to different biomechanical stresses than the GSV. While statins and most other cardiovascular medications have a short half-life (less than 24 hours) 24 and neither parent drugs nor their metabolites were detected in our NMR or LCMS based profiling, it is possible that the above factors confounded the presented results by pharmacological effect. It is, nonetheless, important to stress that despite these issues the varicose vein samples were consistently different from the control groups in the statistical modelling, suggesting that any variability within the non-varicose veins groups was far outweighed by the differences between the two groups.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously studied vein functions in circular segments of human saphenous vein and varicose veins. 50 We have shown that membrane depolarization by high 96 mM KCl solution causes significant contraction of human saphenous vein. Whether membrane hyperpolarization plays a role in human vein relaxation is unclear and should represent an important area for future investigations.…”
Section: Discussionmentioning
confidence: 91%
“…However, to our knowledge, there has been no demonstration of the effect of age on metabolic profile of vein tissue so far. Statins and most of the other cardiovascular medications have a short half-life (less than 24 h) 41 and neither parent statins nor their metabolites were detected in the NMR profiles. Although this does not evade the possibility that an endogenous metabolic response to chronic use of statins might be detected, in light of the nature of the metabolic changes it seems unlikely that statins would be responsible for any of the observed differences in metabolic profile between the varicose vein and control groups.…”
Section: Discussionmentioning
confidence: 97%